The Effectiveness of Group Counselling with Modelling Technique to Improve Self-Efficacy in Senior High School Students Decision Making of Study Continuation (Universitas Negeri Semarang, 2018)
The purpose of this study was to test the effectiveness of group counseling using modeling techniques to improve self-efficacy decision making of study continuation in senior high school students. The research method of present study was experimental design, particular by Randomized Pretest-Postest Comparison Group design, and involving 18 students as participants who selected random assignment from students of class XII SMA Al-Azhar Menganti Gresik. The result of analysis using One way ANOVA showed that group counseling using modeling techniques effective to improve self-efficacy decision making of study continuation in students (F(2,24) = 69.016; p < 0.01). The results of this study indicate that students who received group counseling services with combined techniques experienced improved self-efficacy of advanced study decision making higher than students who received group counseling services with live modeling techniques.